(untitled) (The Pakistan Development Review, 2015)
The curse of poverty had remained a significant problem throughout the history of civilisations. Even in this era of development at least one third of the world population is suffering from the problem of poverty. With such a huge number of human beings living in such a deprived situation, it becomes very crucial to target this issue and search out feasible ways to overcome it. Microfinance has come one of the important tools for reducing poverty. It offers a solution by stimulating economic growth and development. Established microfinance institutions use many instruments to fulfill their promise of poverty reduction. One of those instruments is microcredit. Through this instrument microfinance institutions provide small-scale loans to individuals or groups so that the borrowers could initiate their business and break out of poverty cycle.